2019
DOI: 10.1587/elex.16.20190131
|View full text |Cite
|
Sign up to set email alerts
|

Coagulated region analysis in a microwave surgical device with temperature-dependent physical properties of tissue

Abstract: In surgical devices, it is pointed out that tissues around these devices may experience thermal damage (coagulation). Therefore, evaluating the coagulated region generated by a microwave surgical device is an important issue. In this paper, we estimate the distribution of the coagulated region using numerical calculation. Then, there is a possibility that the calculated results will be affected by change to the electrical and thermal constants during heating. Therefore, the temperature dependence of the tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…where ε r is the relative permittivity of biologic tissue, σ c (S/m) is the electrical conductivity, ω (rad/s) is the angular frequency and ε 0 is the permittivity of vacuum. It has been found that the relative permittivity and electrical conductivity of biological tissues are dependent on frequency, temperature, and water content [63][64][65]. Therefore, taking these factors into consideration is of critical importance to develop an accurate computer model for MWA.…”
Section: Principle Of Mwamentioning
confidence: 99%
“…where ε r is the relative permittivity of biologic tissue, σ c (S/m) is the electrical conductivity, ω (rad/s) is the angular frequency and ε 0 is the permittivity of vacuum. It has been found that the relative permittivity and electrical conductivity of biological tissues are dependent on frequency, temperature, and water content [63][64][65]. Therefore, taking these factors into consideration is of critical importance to develop an accurate computer model for MWA.…”
Section: Principle Of Mwamentioning
confidence: 99%
“…In these simulations we considered the thermal dependence of physical properties of the liver as previously reported in the literature. [36] While the physical and thermal properties of the surrounding tissues were the ones included in the IT'IS Foundation database, [37] the physical properties of the liver were modified according to Manago et al [38] More details can be found in Section S3 of Supporting Information. Figure 5b shows the dependence of 𝜏 relax as a function of the total variation of temperature during cooling (ΔT liver ).…”
Section: In Vivo Transient Thermometry Experimentsmentioning
confidence: 99%
“…However, microwave energy generates large heating region generally [24]. In robotic surgery, localized heating is desirable to avoid damaging the surrounding tissues [25]- [28]. From these backgrounds, we proposed a double-loop antenna for miniaturization and generation of localized heating.…”
Section: Introductionmentioning
confidence: 99%